(untitled) (Revista científica Olimpia, 2021)
Physical Education constitutes an important means to the integral formation of second year students of the English major at the University of Granma. However, a large amount of students show little motivation for this important activity claiming that it doesn’t offer much in terms of the development of language skills. For that, this project is aimed at proposing a set of language games intercalated to the physical activity while the students practicing the foreign language and developing language skills. The project will improve the students’ motivation for Physical Education through the developments of skills in the English Language.